The faith of Israel aspects of Old Testament thought - Rowley, Harold Henry, 1890-1969; James Sprunt Lectures Union Theological Seminary, Richmond, VA, 1955.; Union Theological Seminary, Richmond, VA (London, UK SCM, 1956)
Includes bibliographical references and indexes.
The James Sprunt Lectures delivered at Union Theological Seminary, Richmond, VA, 1955
Keywords: Bible. O.T. -- theology